Setting the stage : Montreal theatre, 1920-1949 - Whittaker, Herbert, 1910-2006 (McGill-Queen's University Press, 1999)
In Montreal Whittaker witnessed the early careers of actors such as Christopher Plummer, Gratien Gélinas, John Colicos, Jean Gascon, Denise Pelletier, and Amelia Hall. He worked in close collaboration with many pioneers of the Little Theatre Movement, the Dominion Drama Festival, and Canadian theatre in general, such as Martha Allan, Charles Rittenhouse, and Pierre Dagenais. His involvement with Dagenais' L'Equipe allows him to report on the early days of francophone theatre in Montreal and the cross-fertilization between Martha Allan's Montreal Repertory Theatre and actor-directors such as Dagenais, Gratien Gélinas, and Yvette Brind'Amour. He also gives us glimpses of the early theatrical spaces in the city that no longer exist, as well as some, such as the Salle de Gésu and the Monument-National, that have survived. This engaging memoir of exciting times is prefaced by a personal tribute from Christopher Plummer and set in context through an introduction, chronology, and bibliography by Jonathan Rittenhouse. Illustrated with a selection of Whittaker's stage and costume designs as well as photographs, Setting the Stage provides a captivating visual record of the period and is a must for everyone interested in Canadian theatre, Canadian arts, culture, and Montreal.